VOLCANIC FACIES ARCHITECTURE OF AN INTRA-ARC STRIKE-SLIP BASIN, SANTA RITA MOUNTAINS, SOUTHERN ARIZONA - Busby C.J.; Bassett K.N. (My University, 2007)
The three-dimensional arrangement of volcanic deposits in strike-slip basins is not only the product of volcanic processes, but also of tectonic processes. We use a strike-slip basin within the Jurassic arc of southern Arizona (Santa Rita Glance Conglomerate) to construct a facies model for a strike-slip basin dominated by volcanism. This model is applicable to releasing-bend strike-slip basins, bounded on one side by a curved and dipping strike-slip fault, and on the other by curved normal faults. Numerous, very deep unconformities are formed during localized uplift in the basin as it passes through smaller restraining bends along the strike-slip fault. In our facies model, the basin fill thins and volcanism decreases markedly away from the master strike-slip fault (“deep” end), where subsidence is greatest, toward the basin-bounding normal faults (“shallow” end). Talus cone-alluvial fan deposits are largely restricted to the master fault-proximal (deep) end of the basin. Volcanic centers are sited along the master fault and along splays of it within the master fault-proximal (deep) end of the basin. To a lesser degree, volcanic centers also form along the curved faults that form structural highs between sub-basins and those that bound the distal ends of the basin. Abundant volcanism along the master fault and its splays kept the deep (master fault-proximal) end of the basin overfilled, so that it could not provide accommodation for reworked tuffs and extrabasinally-sourced ignimbrites that dominate the shallow (underfilled) end of the basin. This pattern of basin fill contrasts markedly with that of nonvolcanic strike-slip basins on transform margins, where clastic sedimentation commonly cannot keep pace with subsidence in the master fault-proximal end. Volcanic and subvolcanic rocks in the strike-slip basin largely record polygenetic (explosive and effusive) small-volume eruptions from many vents in the complexly faulted basin, referred to here as multi-vent complexes. Multi-vent complexes like these reflect proximity to a continuously active fault zone, where numerous strands of the fault frequently plumb small batches of magma to the surface. Releasing-bend extension promotes small, multivent styles of volcanism in preference to caldera collapse, which is more likely to form at releasing step-overs along a strike-slip fault.
Keywords: INTRA-ARC; STRIKE-SLIP BASIN; VOLCANIC FACIES ARCHITECTURE; GLANCE CONGLOMERATE; POLYGENETIC; MULTI-VENT; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская